2015
DOI: 10.1186/s12872-015-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pregnancy induced hypertension and pregnancy outcomes among women seeking maternity services in Harare, Zimbabwe

Abstract: BackgroundPregnancy induced hypertension (PIH) is one of the most common causes of both maternal and neonatal morbidity, affecting about 5 – 8 % of pregnant women. It is associated with adverse pregnancy outcomes as well as maternal morbidity and mortality. Harare City experienced an increase in referrals due to PIH to central hospitals from 2009 to 2011. We conducted a study to determine the prevalence of PIH and pregnancy outcomes among women with PIH.MethodsAn analytic cross sectional study was conducted. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
106
7
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 12 publications
17
106
7
4
Order By: Relevance
“…2,7,15 However, the finding of the study was not comparable with what had been reported by and who reported much higher incidence, although for their respective countries. 18,22,29 The finding of a much lower incidence of GHTN in Nigeria compared to what had been reported by almost a decade ago, could reflect an improvement in antenatal services that has occurred in the country over the years. 22 In addition, this could also reflect regional differences in the incidence of GHTN, as conducted their own study in South-south Nigeria, whereas the present study was conducted in Southeast Nigeria.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…2,7,15 However, the finding of the study was not comparable with what had been reported by and who reported much higher incidence, although for their respective countries. 18,22,29 The finding of a much lower incidence of GHTN in Nigeria compared to what had been reported by almost a decade ago, could reflect an improvement in antenatal services that has occurred in the country over the years. 22 In addition, this could also reflect regional differences in the incidence of GHTN, as conducted their own study in South-south Nigeria, whereas the present study was conducted in Southeast Nigeria.…”
Section: Discussionmentioning
confidence: 40%
“…For instance, in Karachi, reported an incidence of 37%, while found 19.4% in Zimbabwe. 18,29 In Nigeria, found an incidence of 20.8%. 22 On the average, an incidence of 6-7% of GHTN has been reported globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine calcium can be used as a predictive marker for the diagnosis of preeclampsia. Severe morbidity and mortality associated with preeclampsia or eclampsia in the developed countries have been substantially reduced, but they are still a serious and dangerous problem that threatens a safe motherhood particularly in developing countries (2,13). With that in mind, it is important to know the factors that are associated with these disorders and that careful care and treatment of the disease are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…These changes may cause hypertension in people with a history of high blood pressure. The mechanism is though still unknown (1,2). Hypertensive disorders are the most common health complications of pregnancy that occur in 5% to 10% of all pregnancies (3).…”
Section: Introductionmentioning
confidence: 99%